2000
DOI: 10.1073/pnas.180320497
|View full text |Cite
|
Sign up to set email alerts
|

DGD1-independent biosynthesis of extraplastidic galactolipids after phosphate deprivation in Arabidopsis

Abstract: The galactolipids, mono-and digalactosyldiacylglycerol (DGDG), are the most common nonphosphorous lipids in the biosphere and account for 80% of the membrane lipids found in green plant tissues. These lipids are major constituents of photosynthetic membranes (thylakoids), and a large body of evidence suggests that galactolipids are associated primarily with plastid membranes in seed plants. A null-mutant of Arabidopsis (dgd1), which lacks the DGDG synthase (DGD1) resulting in a 90% reduction in the amount of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
350
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(359 citation statements)
references
References 35 publications
9
350
0
Order By: Relevance
“…In plants, phosphate deprivation has been reported to decrease the phospholipid content, consistent with a mobilization of the phosphate reserve, and conversely to increase nonphosphorous membrane lipids such as DGDG and SQDG [3,4]. Moreover a form of DGDG with specific fatty acids: 16:0 at glycerol sn1 position and 18:2 at sn2 position is especially enhanced [5,6].…”
Section: Introductionmentioning
confidence: 90%
“…In plants, phosphate deprivation has been reported to decrease the phospholipid content, consistent with a mobilization of the phosphate reserve, and conversely to increase nonphosphorous membrane lipids such as DGDG and SQDG [3,4]. Moreover a form of DGDG with specific fatty acids: 16:0 at glycerol sn1 position and 18:2 at sn2 position is especially enhanced [5,6].…”
Section: Introductionmentioning
confidence: 90%
“…Thus, the induction of MGD2 and MGD3 expression contributes to a balanced galactolipid biosynthetic pathway to meet the altered fluxes of lipid precursors through the prokaryotic or eukaryotic lipidsynthesizing pathways. In contrast to this scenario, upon phosphate deprivation, MGD2 and MGD3 together with DGD1 and DGD2 are strongly expressed to produce large amounts of DGDG for plastidial and extraplastidial membranes (Härtel et al, 2000;Kelly et al, 2003;Li et al, 2006). During phosphate deprivation, expression of two sulfolipid synthesis genes, SQD1 and SQD2, is induced, resulting in the strong increase in sulfolipid content (Essigmann et al, 1998;Yu et al, 2002), but these alterations were not observed under hypoxia (Supplemental Fig.…”
Section: Galactolipids Seem To Play No Major Role In the Survival Undmentioning
confidence: 98%
“…Germination and seedling growth was carried out in growth chambers at 23°C with a 16-h photoperiod and about 100 mmol photons m -2 s -1 . For phosphate starvation experiments, seedlings grown under control conditions on solidified MS medium were transferred to solidified control (2.5 mM Pi) or Pi-deficient (0 mM Pi) medium (Härtel et al, 2000) at the age of 7 d and grown for another 2 to 10 d. For light/dark treatments on Pi-differing medium, seedlings were transferred to the stress conditions 2 h after the onset of the photoperiod, and for dark incubation, plates were wrapped in aluminum foil immediately after transfer of the seedlings. Growth was continued under long-day conditions for indicated time periods.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon phosphate starvation, plants increase levels of digalactosyldiacylglycerol in roots; this lipid class is believed to functionally replace acidic phospholipids (Härtel et al, 2000). A nonspecific phospholipase C, which hydrolyzes common membrane phospholipids, such as phosphatidylcholine to diacylglycerol, has been shown to increase in expression and activity during phosphate deprivation (Nakamura et al, 2005).…”
mentioning
confidence: 99%